A narrative review of binge eating disorder in adolescence: prevalence, impact, and psychological treatment strategies - Marzilli E; Cerniglia L; Cimino S (Dove Medical Press, 2018)
Eleonora Marzilli,1 Luca Cerniglia,2 Silvia Cimino1 1Department of Dynamic and Clinical Psychology, Psychology and Medicine Faculty, Sapienza – University of Rome, 2Department of Psychology, Psychology Faculty, International Telematic University Uninettuno, Rome, Italy Abstract: Binge eating disorder (BED) represents one of the most problematic clinical conditions among youths. Research has shown that the developmental stage of adolescence is a critical stage for the onset of eating disorders (EDs), with a peak prevalence of BED at the age of 16–17 years. Several studies among adults with BED have underlined that it is associated with a broad spectrum of negative consequences, including higher concern about shape and weight, difficulties in social functioning, and emotional-behavioral problems. This review aimed to examine studies focused on the prevalence of BED in the adolescent population, its impact in terms of physical, social, and psychological outcomes, and possible strategies of psychological intervention. The review of international literature was made on paper material and electronic databases ProQuest, PsycArticles, and PsycInfo, and the Scopus index were used to verify the scientific relevance of the papers. Epidemiological research that examined the prevalence of BED in adolescent samples in accordance with Diagnostic and Statistical Manual of Mental Disorders, 4th Edition showed a prevalence ranging from 1% to 4%. More recently, only a few studies have investigated the prevalence of BED, in accordance with the Diagnostic and Statistical Manual of Disorders, Fifth Edition criteria, reporting a prevalence of ~1%–5%. Studies that focused on the possible impact that BED may have on physical, psychological, and social functioning showed that adolescents with BED have an increased risk of developing various adverse consequences, including obesity, social problems, substance use, suicidality, and other psychological difficulties, especially in the internalizing area. Despite the evidence, to date, reviews on possible and effective psychological treatment for BED among young population are rare and focused primarily on adolescent females. Keywords: binge eating, adolescence, prevalence, impact, treatment